2018
DOI: 10.1002/lary.27303
|View full text |Cite
|
Sign up to set email alerts
|

Irradiated ears in nasopharyngeal carcinoma survivors: A review

Abstract: This article reviews the literature on otological complications in nasopharyngeal carcinoma (NPC) survivals after irradiation during the past three decades. Symptoms of the irradiated ears were assessed from the external ear canal, through the middle ear cavity including the Eustachian tube, and to the inner ear compartments. The development of radioimaging diagnostic techniques, the introduction from adjuvant chemotherapy to concurrent chemoradiotherapy, and the invention of radiotherapeutic equipment to inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 60 publications
(130 reference statements)
1
7
0
3
Order By: Relevance
“…This process may narrow the lumen of vessel and reduce the blood supply, causing severe thrombosis and atherosclerosis. 24 26 In our findings, patients with NPC had a 6.6-fold higher risk of developing postradiation SSHL compared with patients with hypopharyngeal cancer. We further inferred that when the radiation is much closer to the blood supply of the inner ear, more events of SSHL occur.…”
Section: Discussionsupporting
confidence: 49%
“…This process may narrow the lumen of vessel and reduce the blood supply, causing severe thrombosis and atherosclerosis. 24 26 In our findings, patients with NPC had a 6.6-fold higher risk of developing postradiation SSHL compared with patients with hypopharyngeal cancer. We further inferred that when the radiation is much closer to the blood supply of the inner ear, more events of SSHL occur.…”
Section: Discussionsupporting
confidence: 49%
“…13 Although the incidence of ORNTB following primary radiotherapy is less well defined, recent reviews of NPC patients suggest that the condition is relatively rare. 11,25 The latency period between radiation exposure and the development of ORN-related symptoms averages approximately 8 years, but the range varies widely from 6 months to 48 years. 1,4,10,11,[16][17][18][19] In their series of 33 patients, Sharon et al found no correlation between radiation dose to the primary site and the time to development of ORN.…”
Section: Discussionmentioning
confidence: 99%
“…Kronik komplikasyonlar ise sebaseöz ve apokrin bezlerin dejenerasyonu sonucu buşon miktarının azalması ve cilt atrofisi, eksternal otit, DKY stenozu, cilt ülserasyonu, kemik nekrozu ve cilt kanseridir. 7 Bu çalışmada; cilt atrofisi en sık görülen (n=101, %82,7) patolojidir. İkinci sırada kronik eksternal otit (n=5, %4,1) yer almaktadır.…”
Section: Gereç Ve Yöntemlerunclassified
“…Fibrotik, atrofik otitis media ve ileri olgularda kemikçik nekrozu sonucu İTİK oluşabilir. 3,7 Östaki tüpünün geç fibrozisi, farengeal orifiste veya mukozal atrofi sonucu patent tuba östaki de gelişebilir. 8 Bu çalışmada; en sık muayene bulgusu olarak 41 (%33,6) orta kulak normal olarak değerlendirildi.…”
Section: Gereç Ve Yöntemlerunclassified
See 1 more Smart Citation